IMPLEMENTASI KEBIJAKAN PERATURAN MENTERI KESEHATAN NOMOR 23 TAHUN 2014 OLEH DINAS KESEHATAN KABUPATEN BANDUNG - yuspita, widdy; Latifah Rahmi Fauziah; Isnandi Abdul Rozak Riaji (STISIP Widyapuri Mandiri, 2024)
Minister of Health Regulation No. 23/2014 was established in order to improve the degree of public health that underlies the government in ensuring the realisation of individual and community nutrition improvement. Stunting is a crucial nutritional problem. Stunting is a form of growth and development failure that causes linear growth disorders in toddlers. In Bandung Regency in 2019 out of a total of 261,419 under-fives, 5.75% or 15,020 under-fives were categorised as stunted. In 2019 the total number of toddlers in Pacet District was 10,999 toddlers, as many as 227 toddlers (2.1%) were toddlers who were included in the category of short or stunting toddler status. This research uses descriptive methods, namely data collected in the form of words, images, and not numbers. The type of research in this study is descriptive qualitative, namely observation, interview, or document review. Based on the results of the research obtained, the implementation of stunting reduction policies in Pacet Sub-district has been running well as evidenced by the number of stunting sufferers who have decreased every year. Stunting reduction through specific nutrition interventions that contribute 30% is aimed at children in 1000 HPK which is generally carried out by the health sector and is short-term. Meanwhile, stunting reduction through nutrition-sensitive interventions that contribute 70% is aimed at various development activities outside the health sector with the target of the general public, such as conducting counselling to villages where stunting interventions are located in an effort to reduce stunting in Bandung Regency.